PERSEPSI SISWA TERHADAP MANAJEMEN KELAS OLEH GURU DI SMK TRI DHARMA KOSGORO 2 PADANG - Nurleni Hastri Finty Sandi (Jurnal Bahana Manajemen Pendidikan, 2014)
This study aimed to obtain information about classroom management by teachers at SMK Tri Dharma Kosgoro 2 Padang dimensional views of prevention (preventive) and dimensions of healing (curative). The population of this study were 110 students and 90 students were taken with the provisions krecjie table. The research instrument was a Likert scale questionnaire form has been on test validity and reliable. Data were analyzed using the average value (the mean). The results of this study is classroom management by teachers at SMK Tri Dharma Kosgoro 2 Padang dimensional views of prevention (preventive) and dimensions of healing (curative). Kata kunci: manajemen kelas